Effets d'un abreuvement espace (2 et 3 jours) sur la productivite de bovins Boran - Nicholson, M.J. (1986)
A trial conducted to examine the effects of watering Boran cattle once daily, once every two days and once every three days on birth and weaning weights, post-weaning growth and cow performance under extensive grazing conditions.